Board director reputation capital and financial performance of listed firms in Nigeria - Peter Ehizokhale Okpamen; Sunday Oseiweh Ogbeide (Insights into Regional Development)
This study examined the impact of board director reputation capital on financial performance of listed firms in Nigeria. The population of the study consists of all the listed non- financial firms in Nigeria. A sample of fifty (50) firms was selected and data were collected over the period 2007 to 2018. Descriptive statistics and system general method of moment estimation methods were used to undertake the data analysis. Findings reveal that board director reputational capital exerted a positive and significant impact on financial performance of the firms. Board size and firm size were negative on firm financial performance in the reference period. The study concludes that board reputational capital is a significant driver of corporate financial performance in Nigeria irrespective of the size of the board. Based on the empirical findings, it is recommended that there is need for regulators to design a framework to efficiently and effectively monitor the reputation of executive board directors and managers in firms. This will assist to check mate agency costs, demonstration of opportunistic behavior capable of destroying the firm value, There is need for firms to encourage adequate interlocking members who have diverse professional training, high social net worth and experience (experience hypothesis) to positively influence effective management and financial performance of listed firms in Nigeria.